(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Benthic Foraminifera are highly responsive to subtle changes in the estuarine environment. Keeping this in view, a qualitative analysis of living benthic Foraminifera was made of the samples collected from the Mandovi—Zuari estuaries and the connecting long and narrow Cumbarjua canal of Goa. The lower reaches of the rivers are paved with a substrate consisting mostly of sand while it is silty—sand in the upper estuarine zones and clayey in the canal zone. The living Foraminifera are abundant in the upper estuarine zones of the rivers and the Cumbarjua canal junction zones, and characterised by the Ammonia—Trochammina suite with Miliammina fusca; while the canal zone is enriched by agglutinated formes. The Ammonia—Elphidium suite dominates the lower estuarine zones indicating a typical marine environment. The high organic matter content particularly in the Canal Zone is due to the inflow of pollutan ts from the nearby pesticide factory and the constant contaminating discharge of navigating barges and other mechanised boats of the fishing industry. Ammonia sp. and its variants and other agglutinated species become dominant here. The decline in calcareous species and thinning of the dead tests leading to their eventual destruction may be attributed to their susceptibility to acidity in the waters.